I assume you're asked to solve for [tex]a_n[/tex], or find an explicit formula for the n-th term in the sequence.
The sequence is recursively defined by
[tex]\begin{cases} a_1 = 10 \\ a_n = a_{n-1} + 4 & \text{for } n \ge 1 \end{cases}[/tex]
By this definition,
[tex]a_{n-1} = a_{n-2} + 4[/tex]
so that by substitution,
[tex]a_n = (a_{n-2} + 4) + 4 = a_{n-2} + 2\times4[/tex]
and we can repeat this process to find
[tex]a_n = a_{n-3} + 3\times4[/tex]
[tex]a_n = a_{n-4} + 4\times4[/tex]
and so on, down to
[tex]a_n = a_1 + (n-1)\times4[/tex]
Then given the first term [tex]a_1=10[/tex], we have
[tex]a_n = 10 + 4(n-1) \implies \boxed{a_n = 4n + 6}[/tex]